Healthy vs. unhealthy food: A strategic choice for firms and consumers - Fernando Anto\~nanzas; Roberto Rodríguez-Ibeas (Health Economics Review, 2011)
In this paper, we carry out a theoretical analysis of the strategic choice made by firms regarding the type of food they market when they face consumers who care about the healthy/unhealthy attributes of the product but incur in emotional/health costs when the food they consume has unhealthy attributes. We consider a two-stage game. In the first stage, one of the firms chooses the unhealthy content of its product. In the second stage, both firms simultaneously decide their prices. We find that, depending on the parameters of the model, product differentiation can be maximal or less than maximal. The firm that produces the unhealthy food charges a higher price and obtains a larger share of the market unless the emotional/health costs and the unhealthy food production costs are relatively high. We also find that educational campaigns will not always reduce the demand for the unhealthy food or the degree of the unhealthy attribute.
Keywords: I10; I18; L11; 330; healthy food; unhealthy food; obesity; educational campaigns